Catfish (Clarias gariepinus): A Potential Alternative Raw Material for Surimi Production - Zuraida, Ita; Raharjo, Sri; Hastuti, Pudji; Indrati, Retno (Pakistan Journal of Nutrition, 2017)
Background and Objective: The properties of surimi gel are influenced by the fish species used to generate the gel, their chemical compositions and the endogenous enzymatic activity in fish muscle. The aim of this research was to investigate the potential of Clarias gariepinus (local name "lele dumbo") as an alternative raw material for surimi production based on proximate composition, amino acid profile, protein composition and transglutaminase (TGase) and protease activity. Materials and Methods: This study used lele dumbo muscle as the raw material. The chemical properties of proximate composition, amino acid profile, protein composition and endogenous enzyme activity of the sample were determined using standard methods with three replicates. The results were presented as the means±standard deviation. Results: The moisture, ash, crude protein and crude fat content of fish muscle were 73.01±0.05, 0.78±0.02, 16.08±0.03 and 2.03±0.05%, respectively. The lele dumbo muscle has glutamine and lysine residues that can support TGase activity. Myofibrillar proteins were found as the major protein compounds in the fish muscle (16.57±0.03 mgN g–1 muscle) and the sarcoplasmic and stromal protein contents were lower, 4.38±0.03 and 0.71±0.05 mgN g–1 muscle, respectively. The TGase activity of the fish muscle was 0.18 U mL–1 (ΔAbs. = 0.21), which was higher than the protease activity (ΔAbs. = 0.10). Conclusion: Lele dumbo is a potential alternative raw material for surimi production.